(untitled) (Journal of Atomic and Molecular Sciences, 2014)
A novel cyclometalated iridium complex bis[(4-(2-(4-Diphenylamino-phen yl)-benzoinidazol-1-ylmethyl)-phenyl)-diphenyl-amine]iridium(acetylacetonate) Ir(DBPA)_2(acac) is designed and synthesized, and the thermo-stability and photo-physical properties of iridium complex Ir(DBPA)_2(acac) are researched in detail. The complex is functionalized by a bulky non-planarity substituent, thus the phosphorescent concentration quenching in solid state is substantially suppressed, and Ir(DBPA)_2(acac) exhibits bright green-emitting in both solution and solid. The maximum emission peak inr pure solid is about 516 nm, which is slightly blue-shifted in comparison with that in solution. Moreover, the complex Ir(DBPA)_2(acac) exhibits high photoluminescent efficiency and short excited lifetime, indicating it has potential application in fabricating nodoped electrophosphorescence device.